Integration Of Mathematical Number Concepts with Qur'anic Values in Learning - Ainun Mardliyyah; Ratna Dewi Rosyida; Kusno Kusno (Yayasan Rahmat Islamiyah, 2026)
This research aims to examine the relationship between mathematical concepts contained in the verses of the Qur’an and their relevance to the development of holistic and contextual mathematics learning. The method used is a literature study by reviewing Qur’anic verses that include concepts of numbers and mathematical operations, as well as related scholarly works. Data were collected through the identification and classification of Qur’anic verses containing mathematical concepts along with supporting literature. The results show that integrating mathematical principles related to numbers with Qur’anic values in the learning process can deepen students’ understanding of number concepts in a more comprehensive and contextual manner. This article is expected to contribute to the development of a mathematics education model that incorporates Qur’anic values, enabling learning that not only strengthens cognitive understanding of mathematical concepts but also builds students’ character grounded in spiritual values.